2018
DOI: 10.1002/da.22745
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal negative emotion reactivity and cognitive reappraisal on child anxiety disorder

Abstract: This study suggests that maternal NER and reappraisal play an important role in child anxiety and should be considered in prevention and intervention of childhood ADs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Stress makes it more difficult for parents to use appropriate strategies to regulate their own emotional state and behaviors (Crandall et al, 2015 ; Raio et al, 2013 ). As self-regulation influences how parents respond to a child’s negative emotions, and the development of a child’s own regulatory skills (Morris et al, 2017 ), it plays a crucial role in the child’s well-being, including their level of anxiety (Morris et al, 2017 ; Wald et al, 2018 ). Accordingly, less stressed parents can better self-regulate, thus lowering their child’s risk of anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress makes it more difficult for parents to use appropriate strategies to regulate their own emotional state and behaviors (Crandall et al, 2015 ; Raio et al, 2013 ). As self-regulation influences how parents respond to a child’s negative emotions, and the development of a child’s own regulatory skills (Morris et al, 2017 ), it plays a crucial role in the child’s well-being, including their level of anxiety (Morris et al, 2017 ; Wald et al, 2018 ). Accordingly, less stressed parents can better self-regulate, thus lowering their child’s risk of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, Emerson et al (2019) found they were partially explained by reductions in parental experimental avoidance, defined as a parent's difficulty experiencing their child's negative feelings and managing their own reactions to those negative feelings (Tiwari et al, 2008). Correlational data from community-recruited families has shown that mindful parenting is related to child internalizing problems and parental experiential avoidance, cognitive emotion regulation, and beliefs about child anxiety (Burgdorf & Szabó, 2021), which are each related to child internalizing symptoms (Drake & Ginsburg, 2012;Wald et al, 2018). Experimental research showing improvements in these parent variables following a MPP would provide further evidence of how more mindful parenting could explain reduced child internalizing in families of children with primary internalizing concerns.…”
mentioning
confidence: 99%
“…Internalizing problems are also associated with difficulties with emotion regulation (Suveg and Zeman, 2004). For example, greater use by parents of adaptive emotion regulation strategies, such as cognitive reappraisal, are associated with lower youth anxiety (Wald et al, 2018). Since mindful parenting is also associated with greater parental self-regulation (Duncan et al, 2009; Ridderinkhof et al, 2017), mindfulness interventions could reduce youth internalizing problems by facilitating healthier forms of emotional regulation in parents.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when mothers express low levels of negative emotions during a moderately stressful scenario, children's skin conductance response and accelerated heart rate were related to their positive socioemotional functioning (Liew et al., 2003). Relatedly, mothers who report higher levels of negative reactivity (which could be indicative of an inability to suppress) had children who were higher on anxiety (Wald et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of parenting research, maternal CR predicts better child emotion regulation (Tan & Smith, 2019). Parental use of CR is also positively linked to parental warmth (Xiao, Spinrad, & Carter, 2018), while maternal deficits in CR are related to child anxiety disorders (Wald, Carthy, Sehnaar‐Golan, Tadmore‐Zisman, & Ziskind, 2018). Parental ES is negatively related to inductive discipline, child prosocial behavior (Xiao et al., 2018), depressive, and anxiety symptomology (Campbell‐Sills, Barlow, Brown, & Hofmann, 2006a, 2006b; Roemer, Litz, Orsillo, & Wagner, 2001), and positively related to higher maternal internalizing behaviors and infant negative affect (Edwards et al., 2017).…”
Section: Introductionmentioning
confidence: 99%